Detectability of various cannabinoids in plasma samples of cannabis users: Indicators of recent cannabis use?. Issue 10 (1st September 2019) - Kraemer, Michael; Madea, Burkhard; Hess, Cornelius
Abstract : To assess the informative value of determining (minor) cannabinoids in plasma of cannabis users, detection rates of 14 cannabinoids (next to Δ 9 ‐THC and THC‐COOH) were determined. 11‐OH‐THC, THCA, CBC, CBN, and CBD were the most frequent detectable cannabinoids. The dependency of cannabinoid detectability on the plasma Δ 9 ‐THC concentration was examined Abstract: Despite many studies on cannabinoid pharmacokinetics, the proposals of marker cannabinoids for recent cannabis use, and the introduction of mathematical models estimating the time frame between consumption and blood sampling, it is still challenging for forensic toxicologists to estimate the last time of cannabis exposure. To assess the informative value of determining (minor) cannabinoids in plasma of cannabis users, detection rates of 14 cannabinoids next to Δ 9 ‐THC and THC‐COOH (11‐OH‐THC, CBC, CBD, CBN, CBDV, THCV, CBG, CBL, Δ 8 ‐THC, THCA, CBDA, CBGA, THCV‐COOH, CBN‐COOH) were determined. Three hundred fifty‐five plasma samples, previously tested positive for cannabinoids (Δ 9 ‐THC: approximately 0.4 ng/mL – 125 ng/mL (range), mean: 10.1 ng/mL; THC‐COOH: approximately 3.8 ng/mL – 457 ng/mL (range), mean: 71.6 ng/mL) were analyzed by means of liquid chromatography−tandem mass spectrometry (LC–MS/MS). All analyzed cannabinoids could be detected in plasma samples with varying incidence. 11‐OH‐THC, THCA, CBC, CBN, and CBD were the most frequent detectable cannabinoids (next to Δ 9 ‐THC and THC‐COOH). The dependency of cannabinoid detectability on the plasma Δ 9 ‐THC concentration and on the probable time of consumption (estimated by a model of Huestis and coworkers) was examined. Detection incidences (eg, 11‐OH‐THC, CBC) often increased with increasing Δ 9 ‐THC concentration but not for all cannabinoids (eg, CBD, THCA). The presented data for minor cannabinoid findings in plasma can be helpful for a comprehensive interpretation of cannabinoid findings in plasma samples of cannabis users.